África: Diálogo Sur-Sur - Sherifl, Rashid (2024)
Among all converted people to Islam from Africa to Asia, Tunisian women were able to base their struggle for liberation against patriarchal system on thousands of year's history, at the time when they contribute to modern national liberation in T unisia. As a matter of fact, this has been dernonstrated during the victorious peaceful popular uprising reached on January the 14', 201 1 when women threw their decisive strength in the balance opening the way to XXI century struggle for liberation.